Evolutionary Analysis of Makorin Ring Finger Protein 3 Reveals Positive Selection in Mammals. (April 2019) - Ahmad, Muhammad Jamil; Ahmad, Hafiz Ishfaq; Adeel, Muhammad Muzammal; Liang, Aixin; Hua, Guohua; Murtaza, Saeed; Mirza, Riaz Hussain; Elokil, Abdelmotaleb; Ullah, Farman; Yang, Liguo
Makorin ring finger proteins (MKRNs) are part the of ubiquitin-proteasome system; a complex system important for cell functions. Ubiquitin fate through proteolytic, non-proteolytic pathways varies, depending on covalent linkage between ubiquitin and protein substrates. Makorin ring finger protein 3 is an integral part of covalent linkage of ubiquitin to protein substrates. Similar to others imprinted genes, MKRN3 also evolve under positive selection; however, which codons are specifically selected in MKRN3 during evolution are needed to be explored. Different maximum-likelihood (ML) codon-based methodologies were used to ascertain positive selection signatures in 22 mammalian sequences of MKRN3 to probe an individual codon for positive selection signatures. By applying the HyPhy software package implemented in the Data Monkey Web Server and CODEML implemented in PAML, evolutionary analysis based on two Ml frameworks were conducted. The analysis was executed by comparing M1a against M2a, M7 against M8, and PAML models and 2∆Lnl ( LRT ) was resulted by likelihood logs. M1a contributed ω1 ( dN/dS ) with LRT value ( ∆Lnl ) 12.01, and positive selection was found in M2a with ω3 = 2.23603. To further improve selection test, M8 was compared to M7 with 2∆ Lnl ( LRT ) 30.17, and M8 showed positive selection with ω = 1.55759. The data were fit to M8 than M7, which suggests that M8 was the most significant model of selection. M8 was judged encouraging for this analysis and used to establish a positive selection of MKRN3 proteins. We found Gly312 as a positively selected amino acid in a zinc finger motif/Really Interesting New Gene (RING) finger motif; the former ones' region is involved in RNA binding and the later ones in ubiquitin ligase activity of the protein, vital for protein function. Selection analyses of MKRNs might advance the developments in unique approaches that could lead to genetic progress over the selection of superior individuals with the breeding values higher for certain traits as ancestries to get the next generation.